Optimization of Egg Shell Powder and Lime for Waste Soil Improvement at Open Dumping Area Using Monte Carlo Simulations - Pauzi N.I.M.; Aimran M.A.; Ismail M.S.; Radhi M.S.M. (Springer, 2023)
Compressive strength; Intelligent systems; Lime; Mixing; Shells (structures); Soil mechanics; Soils; Stabilization; Egg shell powders; Open dumping area; Optimization value; Soil improvement; Waste soils; Monte Carlo methods